Medical recommendations for home-confined footballers’ training during the COVID-19 pandemic: from evidence to practical application - Eirale, Cristiano; Bisciotti, Giannicola; Corsini, Alessandro; Baudot, Christophe; Saillant, Gerard; Chalabi, Hakim (Biology of Sport, 2020)
In early 2020, the world is facing a global emergency called COVID-19. Many professional footballers around the world are home confined. The maintenance of physical capacity is a fundamental requirement for the athlete, so the training sessions must be adapted to this unique situation. Specific recommendations must be followed concerning the type of training, its intensity, the precautions that have to be followed to avoid the possibility of contagion, and the restrictions in accordance with the presence of any symptoms. This article analyses the available scientific evidence in order to recommend a practical approach.